Exploring Graphene and MoS2 Chips Based Surface Plasmon Resonance Biosensors for Diagnostic Applications - Nurrohman, Devi Taufiq; Wang, Ying-Hao; Chiu, Nan-Fu (Frontiers in Chemistry, 2020)
Until now, two-dimensional (2D) nanomaterials have been widely studied and applied in the biosensor field. Some of the advantages offered by these 2D materials include large specific surface area, high conductivity and easy surface modification. This review discusses the use of 2D material in Surface Plasmon Resonance (SPR) biosensor for diagnostic applications. 2D material reviewed includes graphene and MoS2. The discussion begins with a brief introduction to the general principles of the SPR biosensor. The discussion continues by explaining the properties and characteristics of each material and its effect on the performance of the SPR biosensor in particular its sensitivity. This review concludes with some recent applications of graphene and MoS2 based SPR biosensor in diagnostic applications.